Considerazioni introduttive sul sistema palestinese alla prova del rapporto tra diritto e religioni (Stato, Chiese e pluralismo confessionale, 2024)
Preliminary remarks on the Palestinian legal system to the test of the relation between law and religionsABSTRACT: The aim of this essay is to shape a very first physiognomy of the political and religious Palestinian system. While international current events seem to concentrate especially on the hypotheses of formal State recognition for the Palestinian territories, a different approach to the study of that legal order and the associative forms that make it distinctive might improve the knowledge of the ongoing claims and the petitions for pacification. The analytical purpose consists in underlining a general framework much more articulate and diversified: not a vague, monolithic, block, but an everyday changing combination of interests and belongings never disregarding the relationships between law and religion.SOMMARIO: 1. Una premessa sui contenuti dell’analisi: la necessità di un approccio differente dalle contingenze politiche - 2. Demografia religiosa e pluralità sostanziale in un territorio controverso - 3. Rappresentanza e movimenti sociali: un quadro in divenire - 4. Possibili considerazioni conclusive: la riemersione della statualità e l’attualità delle proposte di autonomia nel dibattito interno e internazionale